2021
DOI: 10.1186/s12876-021-02056-1
|View full text |Cite
|
Sign up to set email alerts
|

Toward finding the difference between untreated celiac disease and COVID-19 infected patients in terms of CD4, CD25 (IL-2 Rα), FOXP3 and IL-6 expressions as genes affecting immune homeostasis

Abstract: Background Coronavirus disease 2019 (COVID-19) is defined as an emerging infectious disease caused by severe acute respiratory syndrome coronavirus 2 and celiac disease (CD) is one of the autoimmune multiorgan diseases, which can be accompanied by an increased risk of viral infections. CD patients, especially untreated subjects, may be at greater risk of infections such as viral illnesses. Interleukin (IL)-6, CD4, CD25, and FOXP3 are known as genes affecting immune homeostasis and relate to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 53 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…People with CD, mainly untreated patients, may be at higher risk for infections such as COVID-19 [ 98 , 161 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…People with CD, mainly untreated patients, may be at higher risk for infections such as COVID-19 [ 98 , 161 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the recently published study by Asri et al, it is suggested that high levels of IL-6 may predispose non-dietary CD patients to severe complications if infected with SARS-CoV-2. In this case, improved expression of CD4, CD25 and FOXP3 as anti-inflammatory markers may be helpful in reducing the serious adverse events of SARS-CoV-2 infection, as demonstrated in the final conclusions of this clinical trial with the control group [ 98 , 179 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies indicated that IL-6 plays an important role in Tfh cell differentiation, and the production of IL-6 by different T-cell types after SARS-CoV-2 infection is beneficial for resolving the viral infection. , As shown in Figure C, at day 7, IL-6 was not elevated in the serum of mice for all groups. However, on day 15, the IL-6 level was significantly elevated in the serum obtained from mice treated with DEVs (Figure C) (DEVs vs DCs or Spike at day 15, p ≤ 0.005, n = 3).…”
Section: Resultsmentioning
confidence: 84%
“…44,45 Interestingly, optimum production of IL-6 and other proinflammatory markers by various cell types after SARS-CoV-2 infection provided a positive indication in resolving the viral infection. 21 It is important to note that although DEVs induce antibodies at early time points, however, the antibody level becomes equivalent at later stages, as observed with DCs and Spike. A similar observation was also correlated with the ability to neutralize the virus in an in vitro model.…”
Section: Synthesis and Characterization Of Devs From Bonementioning
confidence: 93%